Clinical Significance of Early Carcinoembryonic Antigen Change in Patients With Nonmetastatic Colorectal Cancer - Jo, Younghoo; Lee, Jae-Hoon; Cho, Eun-Suk; Lee, Hye Sun; Shin, Su-Jin; Park, Eun Jung; Baik, Seung Hyuk; Lee, Kang Young; Kang, Jeonghyun (Frontiers in Oncology, 2022)
Background This study aimed to evaluate the prognostic significance of preoperative, postoperative, and trajectory changes in carcinoembryonic antigen (CEA) levels in patients with colorectal cancer (CRC). Methods This retrospective study included patients who underwent surgical resection for nonmetastatic CRC. The optimal cutoff values of preoperative CEA (CEA-pre), early postoperative CEA (CEA-post), and CEA level change (CEA-delta) were determined to maximize the differences in overall survival (OS) among groups. The patients were divided into three groups according to CEA-trend: normal, low CEA-pre; normalized, high CEA-pre/low CEA-post; elevated, high CEA-pre/high CEA-post. The integrated area under the curve (iAUC) was used to compare the discriminatory power of all variables. Results A total of 1019 patients diagnosed with stage I–III CRC were enrolled. The optimal cutoff values of CEA level were determined as 2.3 ng/mL for CEA-pre, 2.3 ng/mL for CEA-post, and -0.93 ng/mL for CEA-delta. Although subgroup dichotomization showed that CEA-pre, CEA-post, CEA-delta, and CEA-trend were all associated with OS in univariate analysis, CEA-trend was the only independent prognostic factor in multivariate analysis. The iAUC of CEA-trend was superior to that of CEA-pre, CEA-post, and CEA-delta. Compared with the normal group, the normalized group showed worse OS (p=.0007) in stage II patients but similar OS (p=.067) in stage III patients. Conclusion The optimal cutoff value of CEA level in the preoperative and postoperative periods was determined to be 2.3 ng/mL, and the combination of CEA-pre and CEA-post showed better prognostic stratification. However, its prognostic significance may differ depending on the CRC stage.